Exploring the health benefits of Ganoderma: antimicrobial properties and mechanisms of action - Karunarathna, Samantha C.; Patabendige, Nimesha M.; Hapuarachchi, Kalani K.; Promputtha, Itthayakorn (Frontiers in Cellular and Infection Microbiology, 2025)
Ganoderma, a well-known medicinal mushroom, has garnered attention for its broad therapeutic properties, particularly its potent antimicrobial activities. This review focuses on the mechanisms of action and bioactive compounds responsible for the ability of Ganoderma to inhibit various pathogenic microorganisms. The polysaccharides, triterpenoids, proteins, and phenolic compounds in Ganoderma exhibit strong antimicrobial effects by targeting bacterial cell walls, disrupting membrane integrity, and inhibiting key microbial enzymes. These compounds are effective against a wide range of bacteria, including Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and various fungi. Triterpenoids, specifically, have demonstrated efficacy in modulating immune responses, further enhancing the body’s defense mechanisms against infections. Furthermore, the role of Ganoderma in preventing biofilm formation and combating antibiotic-resistant strains highlights its potential as a natural antimicrobial agent. While in vitro and in vivo studies strongly support the antimicrobial properties of Ganoderma, future resety -50arch should focus on large-scale clinical trials to confirm its efficacy and explore its synergistic effects with conventional antibiotics. Establishing standardized dosages and exploring the molecular pathways of its antimicrobial actions will be key to incorporating Ganoderma into clinical practice for infection control.